2018
DOI: 10.1186/s12864-018-5250-4
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive proteome analyses of lysine acetylation in tea leaves by sensing nitrogen nutrition

Abstract: BackgroundNε-Acetylation of lysine residues, a frequently occurring post-translational modification, plays important functions in regulating physiology and metabolism. However, the information of global overview of protein acetylome under nitrogen-starvation/resupply in tea (Camellia sinensis) leaves was limited. And the full function of lysine acetylated proteins of tea plants in nitrogen absorption and assimilation remains unclear.ResultsHere, we performed the global review of lysine acetylome in tea leaves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
5
48
1
Order By: Relevance
“…By GO functional analysis of the acetylated proteins, we found “protein binding” was one of the most abundant terms in the MF category in A. japonicus , which was consistent with the findings in bacteria [23], plants [25], and mammals [24]. The terms associated with “ribosome”, “nucleus”, “cytoplasm”, and “membrane” were enriched in the CC category, which suggested the wide distribution of lysine acetylated proteins [25]. The acetylated proteins we identified also represented a wide range of BP terms.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…By GO functional analysis of the acetylated proteins, we found “protein binding” was one of the most abundant terms in the MF category in A. japonicus , which was consistent with the findings in bacteria [23], plants [25], and mammals [24]. The terms associated with “ribosome”, “nucleus”, “cytoplasm”, and “membrane” were enriched in the CC category, which suggested the wide distribution of lysine acetylated proteins [25]. The acetylated proteins we identified also represented a wide range of BP terms.…”
Section: Discussionsupporting
confidence: 87%
“…Sequence logos showed that lysine was over-represented immediately around acetylated lysine in A. japonicus . The preference was also observed in many other species [25,26]. These motifs may be specially recognized by diverse lysine acetyltransferases (KATs).…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, previous study in our laboratory showed that the levels of lysine acetylation in tea leaves changed dynamically under NH 4 + resupply. And lysine acetylated proteins might regulate photosynthesis, glycolysis and secondary metabolism in tea leaves after NH 4 + resupply [5]. However, the global profiling of lysine crotonylated proteins in tea plants in response to NH 4 + resupply remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Tea plant cultivar, ‘QN3’ ( Camellia sinensis cv. QN3) is an improved cultivar bred by the Tea Research Institute, Qingdao Agricultural University 43 45 . The 2-year-old tea seedling were cultured in growth chamber for 2 weeks with photoperiod (12 h light at 25°C and 12 h dark at 20°C, 75% of humidity) and a light intensity of 18, 000 lx.…”
Section: Methodsmentioning
confidence: 99%